One Size Fits All? Heckscher-Ohlin Specialization in Global Production - Schott, Peter K (American Economic Review, 2003)
This paper introduces a new technique for testing the Heckscher-Ohlin model that allows for the possibility that countries with sufficiently disparate endowments specialize in unique subsets of goods. Results based upon industry-level data reject one-size-fits-all homogeneity in favor of Heckscher-Ohlin specialization. Results also reveal that industry-level data hide substantial intra-industry heterogeneity, violating the assumptions of the model and complicating the interpretation of results from earlier research. A methodology for adjusting industry output to reflect underlying product variation is introduced. Reestimation of the model using adjusted aggregates in place of standard industry classifications provides strong support for Heckscher-Ohlin specialization.